Analysis of Banana Dempo Business Development in South Poleang District, Bombana Regency - Aldi Hidayat; Sarinah Sarinah; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the strategy of developing a banana dempo business with a SWOT analysis in Poleang Selatan District, Bombana Regency. Determination of the research location was done purposively. Data was collected by using questionnaires, interviews, and documentation methods. The analysis used is a SWOT analysis. Based on the study results, the internal strength factor with the highest score of 0.60 is the variety and quality of the banana dempo product with a weight value of 0.15 twigs 4. The internal weakness factor with the lowest score of 0.05 is that product promotion activities are not carried out with a weight value of 0.05 branches 1. External opportunity factor with the highest score of 0.45, namely products that become typical souvenirs with a weight value of 0.15 with twigs 3. External threat factor with the lowest score of 0.15 the price of raw materials is increasing with a weight value of 0.15 twigs 1. The strategies generated in the prospect of developing the banana dempo business "UD Rahmat" in Batu Putih Village, Poleang Selatan District are SO (1) strategies to maintain the quality of banana chips products made from natural, quality, and nutritious raw materials to meet the demand for banana chips, (2) increase the amount of production and quality of banana Dempo to meet market demand, (3) increasing promotion and (4) utilizing government assistance in reducing production costs), WO strategy ((1) increasing and strengthening marketing network and (2) improving business management system), ST strategy (1) Ensuring availability of primary raw materials continuously and (2) implementing production cost efficiency), and the WT strategy (1) increasing the ability to use modern technology in product innovation and (2) increasing the motivation of business actors in improving production quality).